The universal journalist. - Randall, David, 1951-2021 (London : Pluto, 2011)
This is a new edition of the world's leading textbook on journalism. Translated into more than a dozen languages, David Randall's handbook is an invaluable guide to the 'universals' of good journalistic practice for professional and trainee journalists worldwide. Irrespective of language or culture, good journalists share a common commitment to the search for truth, often in difficult circumstances. David Randall emphasises that good journalism isn't just about universal objectives: it must also involve the acquisition of a range of skills that will empower journalists to operate in an industry where ownership, technology and information are constantly changing. This acclaimed handbook challenges old attitudes, procedures and techniques of journalism where they are seen as cynical and sloppy. A raft of new anecdotes, wisdom and warnings covering privacy, celebrity culture and the impact of the internet make this edition an essential companion for journalists in the digital age.
Keywords: Journalistiek